Więzienni lekarze. Opieka lekarska w więzieniach stalinowskich w latach 1945–1956 - Machcewicz, Anna (Pamięć i Sprawiedliwość, 2014)
The article is an attempt at presenting the role of doctors working in the reality of prisons in the years 1944–1956. Medical care was supposed to be limited to a minimum, and doctors had to serve a specific role in supervising the prisoners. On the one hand, they were part of the oppressive system, while on the other hand, they often stepped outside their assigned roles, helping the prisoners and mitigating the regime. As in other aspects of Stalinism, here the reality also luckily turned out to be more human than the official assumptions.People who worked in prisons were civilian doctors and nurses employed on contract by the Prison System Department, as well as military doctors assigned to this work as part of their service. Due to constant lack of medical staff willing to work in prison hospitals and infirmaries, doctors serving sentences and medical students were employed, as well. Of course, their situation was much worse than of the “freedom” doctors. Both groups, however, were subject to control by prison officers, in particular of the Special Department which oversaw the work of prison intelligence and tracked all attempts to make informal contact with the prisoners.Prison healthcare was part of the system and its political objectives and ideological vision of the enemy, but it was also a derivative of the economic situation in the war-ravaged country. In the years 1944–1956, medical care in Polish prisons evolved. In the first years after the war, the health of prisoners was affected by terrible sanitary conditions, lack of doctors and basic medical supplies. Although over the years the equipment of some hospitals and drug supplies improved, poor health of prisoners was primarily affected by the long-term repressive regime which began to weaken only in the middle of 1953. The article is based on documents of the MBP Prison System Department, testimonies of prison doctors before the court and prosecutors, published memoirs of prisoners, as well as the author’s own interviews with doctors who were prisoners.